2015
DOI: 10.22256/pubvet.v7n19.1601
|View full text |Cite
|
Sign up to set email alerts
|

Importance of choosing a program receiving embryo transfer in cattle

Abstract: ResumoA utilização de biotecnologias reprodutivas representa cada vez mais a evolução da produção animal no Brasil e no mundo. A Inseminação Artificial em bovinos veio como a pioneira dessa evolução, seguida pela Transferência de Embriões (TE) convencional que trouxe a Aspiração Folicular guiada por ultra-sonografia para produção in vitro de embriões bovinos, possibilitando o incremento da genética dos rebanhos, em quantidade e qualidade.Objetivou-se descrever os aspectos relacionados a um programa de transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Attention on the health, nutrition, and wellbeing of the recipient cows is essential for them to respond to the hormonal treatments required for FTET to result in one deliver per year and in heavy, healthy weaned calves (HONORATO et al, 2013). The management of the recipient cows used in the present study may explain the pregnancy rates found after ET of Nellore IVPE, which were higher than those found in similar studies (ANDRADE et al, 2012;LEAL et al, 2009;SCANAVEZ;CAMPOS;SANTOS, 2013;PUPULIM et al, 2010;MOSCHINI;BARREIROS, 2016;SILVA et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Attention on the health, nutrition, and wellbeing of the recipient cows is essential for them to respond to the hormonal treatments required for FTET to result in one deliver per year and in heavy, healthy weaned calves (HONORATO et al, 2013). The management of the recipient cows used in the present study may explain the pregnancy rates found after ET of Nellore IVPE, which were higher than those found in similar studies (ANDRADE et al, 2012;LEAL et al, 2009;SCANAVEZ;CAMPOS;SANTOS, 2013;PUPULIM et al, 2010;MOSCHINI;BARREIROS, 2016;SILVA et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the variables that affect the production of viable in vitro-produced embryos, the selection of donors and recipient females should be carefully conducted to generate positive results during pregnancy (Honorato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%